Nutritional and physiological impact of dietary marula (Sclerocarya birrea ssp. caffra) kernel cake as a soybean meal replacement in Jumbo quail: implications for meat quality and consumer health - Mcolisi Ngcamphalala; Makiwa S. Mthana; Doctor M.N. Mthiyane; Victor Mlambo (Journal of Agriculture and Food Research, 2025)
The high feed costs, primarily due to reliance on expensive imported soybean meal (SBM) as a dietary protein source, limit the economic sustainability of quail production. Thus, this study evaluated marula (Sclerocarya birrea ssp. caffra) kernel cake (MKC) as a sustainable alternative dietary protein source for quail. In a completely randomized design, 400 male Jumbo quail were randomly allocated to five experimental diets formulated by replacing 0 %, 25 %, 50 %, 75 %, and 100 % of SBM with MKC. Eight replicate cages (experimental units) per diet, each housing 10 birds for 4 weeks, were used. Whereas diet did not affect body weight gain (BWG), feed conversion efficiency (FCE), carcass characteristics, internal organs, haemato-biochemistry, and some meat quality parameters, incremental dietary levels of MKC linearly decreased quail feed intake (FI) (linear: P < 0.01) and tended to increase their gizzard weights (linear: P = 0.055). Also, meat stearic, oleic, and tricosanoic acids linearly increased (P < 0.05), while myristic, palmitic, palmitoleic, linoleic, and α-linolenic acids decreased (P < 0.05) as MKC levels increased. Complete replacement of SBM with MKC enhanced the levels of stearic and oleic acids in quail meat, which benefits consumer health. However, this was accompanied by a progressive decline in linoleic and α-linolenic acids as dietary MKC levels increased, raising potential nutritional concerns. In conclusion, replacing SBM with MKC resulted in no differences in BWG, FCE, or carcass yields, demonstrating the potential of MKC as a viable alternative dietary protein source that does not compromise quail performance.